Emplacement of the Slaufrudalur Pluton, southeast Iceland, deduced from field observations and its three-dimensional shape - Burchardt, S.; Tanner, D. C.; Krumbholz, M. (TRABAJOS DE GEOLOGÍA, 2009)
The margin of the excellently exposed, granitic Slaufrudalur Pluton was mapped with high resolution GPS. Based on the GPS data, we reconstructed its three-dimensional shape, which resembles an elongated rhomboid with subvertical walls and a flat roof at map-scale. At outcrop-scale, the roof contact is characterised by numerous steps and cuspate indentations interpreted as signs of magmatic stopping. From this, we conclude that the main volume of the pluton was created by cauldron subsidence, whereas the roof was subsequently reshaped by magmatic stopping.